PENGARUH PENERAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Tanod, Kleysia N.; Nangoi, Grace B.; Suwetja, I Gede (Universitas Sam Ratulangi, 2019)
Corporate Social Responsibility is a form of corporate responsibility towards shareholders, parties with an interest in the company and the community. CSR is also an important factor that is the basis for investors' consideration to make investment decisions on the company so that the company can manage investor capital to carry out company activities to achieve profits. This study aims to determine the effect of corporate social responsibility on corporate profitability, this study uses the ratio of return on assets and return on equity to calculate the company's profitability. This research uses quantitative research method with simple linear regression, where this study uses only 1 independent variable and 2 dependent variables. The population use in this study are manufacturing company listed on the Indonesia Stock Exchange in 2013-2017. The sample of this study used 59 manufacturing companies that met the sample selection criteria. Sample selection uses purpose sampling technique. The results show that corporate social responsibility has a significant effect on return on assets and return on equity.